2021
DOI: 10.1002/ctm2.522
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C‐II induces EMT to promote gastric cancer peritoneal metastasis via PI3K/AKT/mTOR pathway

Abstract: Background Peritoneal metastasis (PM) occurs frequently in patients with gastric cancer (GC) and confers poor survival. Lipid metabolism acts as a non‐negligible regulator in epithelial–mesenchymal transition (EMT), which is crucial for the metastasis of GC. As apolipoprotein C2 (APOC2) is a key activator of lipoprotein lipase for triglyceride metabolism, the exact mechanism of APOC2 remains largely unknown in GC. Methods Tandem mass tags identified differentially expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 72 publications
(144 reference statements)
0
41
0
Order By: Relevance
“…More and more molecules regulating lipid metabolism have been proved to promote tumor metastasis by regulating EMT, including apolipoprotein C, sterol regulatory element‐binding transcription protein 1, stromal‐interaction molecule 1, human hydroxysteroid dehydrogenase‐like 2, and cytosolic phospholipase A2α. 243 , 244 , 245 , 246 In triple‐negative breast cancer, nicotinamide adenine dinucleotide phosphate (NADP) steroid dehydrogenase‐like (NSDHL), a cholesterol metabolic enzyme, has been reported to be a potential metastatic driver. 247 The functions of NSDHL rely on its enzyme activity in the biosynthesis of cholesterol and is mediated by the NSDHL‐TGFβR2 signaling pathway.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%
“…More and more molecules regulating lipid metabolism have been proved to promote tumor metastasis by regulating EMT, including apolipoprotein C, sterol regulatory element‐binding transcription protein 1, stromal‐interaction molecule 1, human hydroxysteroid dehydrogenase‐like 2, and cytosolic phospholipase A2α. 243 , 244 , 245 , 246 In triple‐negative breast cancer, nicotinamide adenine dinucleotide phosphate (NADP) steroid dehydrogenase‐like (NSDHL), a cholesterol metabolic enzyme, has been reported to be a potential metastatic driver. 247 The functions of NSDHL rely on its enzyme activity in the biosynthesis of cholesterol and is mediated by the NSDHL‐TGFβR2 signaling pathway.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%
“…The PI3K signaling pathway has long been a focus of interest in cancer due to its role in cancer cell proliferation, migration and metabolism. It is also related to lipid metabolism in many cancers such as gastric cancer [ 57 ], hepatocellular carcinoma [ 58 ] and breast cancer [ 59 ]. Recent reports have showed that the activation of the PI3K signaling pathway is linked to lipid synthesis [ 43 ] and lipid droplet accumulation [ 60 ] in OC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overexpression of TNFAIP6 was also found to increase with tumor invasion and lymph node metastasis in gastric cancer [ 44 ]. Apolipoprotein C2 (APOC2) is a lipoprotein lipase activator involved in fatty acid metabolism [ 45 ]. Most differentially expressed lncRNAs, such as AL121906.2 [ 46 ], AC092910.3 [ 47 ], AC005332.4 [ 48 ], and CASC9 [ 49 ], were upregulated in EAC subtype 1 and had been previously reported as prognostic biomarkers in multiple tumors.…”
Section: Discussionmentioning
confidence: 99%